MORAL RIGHTS AND CANADIAN COPYRIGHT REFORM: THE IMPACT ON MOTION PICTURE CREATORS - Herman, Jonathan (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 1990)
The traditional rights of an artist to preserve his monopoly on the financial exploitation of his work, now take their place alongside newly expanded moral rights introduced by the reform of Canada's Copyright Act in 1988. Moral rights are inspired by the European doctrine that art is the extension of the creator's personality and they include the rights to divulge, to claim authorship and to maintain the integrity of artistic work.These new "rights of personality" appear to apply equally to all artists. In practice, however, the Act's provision for waiving moral rights could lead to diminished protection for employee-creators. The author suggests that this is particularly true in the collaborative arts such as motion picture production where unequal bargaining conditions between creators and producers are likely to prevail.